Financial Performance Analysis of Investor Reactions with Sustainability Reports as a Moderating Variable in Mining Companies Listed on The IDX - Rosyid, Adam Ibnu; Kusuma, Dheni Indra; Hapsoro, Dody (Universitas Kristen Maranatha, 2024)
Abstract Purpose - This study aims to analyze financial performance on investor reaction with sustainability report as a moderator. Sustainability report is proxied by sustainability report disclosure index (SRDI), financial performance is proxied by 4 measures namely ROA, CR, TAT and DER, then investor reaction is proxied by stock returns. Design/methodology/approach - The population of research used is mining companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The study used purposive sampling technique in determining the research sample. From a population of 60 mining companies, 15 companies were obtained that met the predetermined sample criteria with the observation period 2019-2021. The analysis method used is Moderated Regression Analysis (MRA). Findings - The results showed that financial performance based on ROA proxies has a positive effect on investor reactions and TAT has a negative effect on investor reactions. Financial performance based on CR and DER proxies has no effect on investor reactions. The results also show that the sustainability report is able to moderate the effect of financial performance based on ROA proxies on investor reactions, but the sustainability report is not able to moderate the effect of financial performance based on CR, TAT and DER proxies on investor reactions. This shows that investors still value ROA as a reference in assessing the financial performance of mining companies. Sustainability reports are proven to be a factor that moderates ROA on investor reactions. Mining companies may start to consider sustainability reports to attract investor reaction.Research limitations/implications – The results of this study cannot be generalized because the scope of this research is limited to the mining industry. Keywords: Financial Performance, Sustainability, and Investor Reaction